Pengaruh Tipe Kepemimpinan dan Budaya Organisasi terhadap Motivasi Kerja Pegawai Kecamatan Lowokwaru Kota Malang - Fikri, Fikri (Jurnal Aplikasi Manajemen, 2008)
This study was subjected to analysis the leadership type and organizational culture that influence the work motivation of employee. This research done in Kecamatan Lowokwaru office. Malang city by sample at about 30 employee by using census method. By using multiple regression method got the result as follow; a) leadership style and organization culture have effect for employee motivation, b) partially, leadership style has effect the employee motivation.